E-learning as a Strategy to Qualify Health Professionals on the covid-19 Pandemic - Evelyn de Britto Dutra; François Isnaldo Dias Caldeira; Erica Tatiane Da Silva; Kellen Cristina da Silva Gasque (ULAKES JOURNAL OF MEDICINE, 2026)
Abstract: This scoping review aimed to map and analyze the e-learning educational strategies developed worldwide to train and qualify health professionals in response to the COVID-19 pandemic, covering the period from the World Health Organization’s declaration of the pandemic on March 11, 2020, to March 2022, which marked two years since its declaration. A Scope Review, based on the Joanna Briggs Institute method, was conducted to identify educational strategies published from 2020 to March 2022. The databases searched included PubMed, VHL, ERIC, CINAHL, PROSPERO, and OSF. Eight studies that highlighted educational strategies covid-19-themed were included. Notably, 75% of the articles correspond to the year 2021, with 37.5% of the research produced in the United States. Regarding the nature of the study, 50% are quantitative. Continuing education for health professionals in a general context appears in 75% of the articles, while 25% focus on course format. The selected studies offer a broad view of the educational strategies carried out through e-learning for the qualification of health professionals in response to the covid-19 pandemic, including courses, gamified modules, webinars, training sessions, tele simulation, and telehealth.